2015
DOI: 10.3390/md13106038
|View full text |Cite
|
Sign up to set email alerts
|

New Kunitz-Type HCRG Polypeptides from the Sea Anemone Heteractis crispa

Abstract: Sea anemones are a rich source of Kunitz-type polypeptides that possess not only protease inhibitor activity, but also Kv channels toxicity, analgesic, antihistamine, and anti-inflammatory activities. Two Kunitz-type inhibitors belonging to a new Heteractis crispa RG (HCRG) polypeptide subfamily have been isolated from the sea anemone Heteractis crispa. The amino acid sequences of HCRG1 and HCRG2 identified using the Edman degradation method share up to 95% of their identity with the representatives of the HCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 58 publications
3
40
0
Order By: Relevance
“…Nevertheless, a slightly higher value of K i for rHCRG21 compared to those of APHC1–APHC3, can be explained by the presence of a N-terminal Arg, which noticeably increases the energy of Kunitz-type H. crispa peptides binding with proteases. This energy benefit has been shown previously by computational methods for HCRG1 and HCRG2 [18] (Table 1). …”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Nevertheless, a slightly higher value of K i for rHCRG21 compared to those of APHC1–APHC3, can be explained by the presence of a N-terminal Arg, which noticeably increases the energy of Kunitz-type H. crispa peptides binding with proteases. This energy benefit has been shown previously by computational methods for HCRG1 and HCRG2 [18] (Table 1). …”
Section: Resultssupporting
confidence: 82%
“…To date, a number of highly homologous native serine protease inhibitors has been isolated from different species: Anemonia sulcata [7,13], Heteractis crispa [14,15,16,17,18], Anthopleura aff. xanthogrammica [19,20], Anthopleura fuscoviridis [21], Stichodactyla helianthus [22,23,24], and Stichodactyla haddoni [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…856 Absolute congurations were assigned by stereoselective synthesis of the corresponding enantiomers, with the magnitudes of optical rotation observed indicating the natural products had been isolated as scalemic (partially racemic) mixtures. Further studies of toxins from anemones has revealed two new examples of HCRG polypeptides (>6 kDa) from Heteractis crispa, 857 the toxicity of the a-pore-forming toxin equinatoxin II depends upon its ability to assemble into oligomers on the cell surface, 858 while N-terminus modied analogues of the 35-residue disulderich toxin ShK from Stichodactyla helianthus showed enhanced selectivity towards voltage-gated potassium channel Kv1.3 versus other subtypes, making them of clinical interest for the treatment of autoimmune diseases. alignment study of cnidarian toxins suggests a common origin of sodium channel and a subtype of potassium channel toxins in sea anemones and that pore-forming toxins have evolved under strong evolutionary constraints.…”
Section: Cnidariansmentioning
confidence: 99%